Caracterização e avaliação da qualidade da água de sistema intensivo deprodução de camarão com bioflocos em diferentes salinidades - Anna Carolina Ferreira Spelta (2016)
The aim of this study was to characterize and evaluate the water quality of intensive farming of marine shrimp (Litopenaeus vannamei) in two different salinities using biofloc system in laboratory. There were employed two treatments, 8 salinity (T8) and 16 (T16), with four replicates each and density of 250 individuals/m². During 60 days, physicochemical analyses were carried out in the water of cultivation, in the sludge removed by the clarifier and also in the molasses. The growth performance of animals was also evaluated in each tank. Regarding the physicochemical parameters, the following average results were observed for T16 and T8: 5.49 ± 0.49 and 5.81 ± 0.33 mg/L for dissolved oxygen (DO); 80.22 ± 7.33 and 85.13 ± 4.67% for saturated oxygen (OSAT); 27.54 ± 1.14 and 27.81 ± 0.96°C for water temperature (T water); 7.67 ± 0.22 and 7.76 ± 0.28 for pH; 120.06 ± 23.27 and 93.69 ± 18.30mg/L of CaCO3 for total alkalinity (AT); 44.26 ± 27.74 and 47.66 ± 20.40 mg/L for biochemical oxygen demand (BOD); 1,338.28 ± 499.147 and 1,288.15 ± 492.58 mg/L for chemical demand total oxygen (DQOt); 1,278.13 ± 558.35 and 746.202 ± 299.73 mg/L filtered chemical oxygen demand (DQOf); 17,499.99 ± 1249.38 and 8,871.85 ± 995.09 mg/Ltotal solids (TS); 15,092.74 ± 974.28 and 6,848.37 ± 735.61 mg/L for fixed total solids (STF); 2,353.88 ± 361.49 and 2,009.95 ± 405.35 mg/L for total volatile solids (STV); 882.73 ± 200.04 and 914.02 ± 257.98 for total suspended solids (TSS); 497.91 ± 146.24 and 647.88 ± 206.81 mg/L of volatile suspended solids (VSS); 384.81 ± 85.30 and 266.57 ± 81.68 mg/L for fixed suspended solids; 47.07 ± 24.22 and 51.39 ± 25.80 mL/L for settleable solids (ssed); 6.74 ± 1.00 and 6.56 ± 0.92 mg/L of nitrate (NO3 -); 0.46 ± 0.26 and 0.51 ± 0.40 mg/L of nitrite (NO2 -); 0.76 ± 0.44 and 1.11 ± 0.78 mg/L for total ammonia (TA); 3.86 ± 1.00 and 4.02± 0.88 mg/L of phosphate (PO4 3-). Regarding the growth performance of shrimp, they were checked for T16 and T8, weight gain of 5.99 ± 0.54 and 2.91 ± 0.93 g; specific growth rate of 1.64 ± 0.13 and 0.82 ± 0.27%/day; mortality of 14.7 ± 2.52 and 24 ± 4.12%; Final biomass 338.46 ± 37.12 and 147.93 ± 47.2 g; and feed conversion of 1.7 ± 0.23 and 1.7 ± 0.93,respectively. From these results it was concluded that high concentrations of organic matter, total and suspended solids, nitrogen and phosphate were observed in both salinities, demonstrating a need for methods of treatment integrated into the cultivation systems, inorder to avoid deterioration in quality water, both for shrimp, and for the release into water bodies. Moreover, it was possible to produce marine shrimp in continental regions with artificial brackish water. Thus, it was observed that at higher salinities shrimp growth was favored and mortality was reduced.